Utility of a Novel Three-Dimensional and Dynamic (3DD) Cell Culture System for PK/PD Studies: Evaluation of a Triple Combination Therapy at Overcoming Anti-HER2 Treatment Resistance in Breast Cancer - Ande, Anusha; Vaidya, Tanaya R.; Tran, Bao N.; Vicchiarelli, Michael; Brown, Ashley N.; Ait-Oudhia, Sihem (Frontiers in Pharmacology, 2018)
Background: Emergence of HER2 therapy resistance in HER2-positive (HER2+) breast cancer (BC) poses a major clinical challenge. Mechanisms of resistance include the over-activation of the PI3K/mTOR and Src pathways. This work aims to investigate novel combination therapy that employs paclitaxel (PAC), a mitotic inhibitor, with everolimus (EVE), an mTOR inhibitor, and dasatinib (DAS), a Src kinase inhibitor, as a modality to overcome resistance. Methods: Static (two dimensional, 2D) and three-dimensional dynamic (3DD) cell culture studies were conducted using JIMT-1 cells, a HER2+ BC cell line refractory to HER2 therapies. Cell viability and caspase 3 expression were examined after JIMT-1 cell exposure to agents as monotherapy or in combination using a 2D setting. A pharmacokinetic/pharmacodynamic (PK/PD) combination study with PAC+DAS+EVE was conducted over 3 weeks in a 3DD setting. PAC was administered into the system via a 3h infusion followed by the addition of a continuous infusion of EVE+DAS 24 h post-PAC dosing. Cell counts and caspase-3 expression were quantified every 2 days. A semi-mechanistic PK/PD model was developed using the 2D data and scaled-up to capture the 3DD data. The final model integrated active caspase-3 as a biomarker to bridge between drug exposures and cancer cell dynamics. Model fittings were performed using Monolix software. Results: The triple combination significantly induced caspase-3 activity in the 2D cell culture setting. In the 3DD cell culture setting, sequential dosing of PAC then EVE+DAS showed a 5-fold increase in caspase-3 activity and 8.5-fold decrease in the total cell number compared to the control. The semi-mechanistic PK/PD models fit the data well, capturing the time course profiles of drug concentrations, caspase-3 expression and cell counts in the 2D and 3DD settings. Conclusion: A novel, sequential triple combination therapeutic regimen was successfully evaluated in both 2D and 3DD in vitro cell culture systems. The efficacy of this combination at inhibiting the cellular proliferation and re-growth of HER2/mTOR resistant cell line, JIMT-1, is demonstrated. A biomarker linked PK/PD model successfully captured all time-course data. The latter can be used as a modeling platform for a direct translation from 3DD in vitro settings to the clinic.